Effect of Liquid Marble 3D Culture System on In Vitro Maturation and Embryo Development of Prepubertal Goat Oocytes - Andrea Podda; Linda Dujíčková; Federica Ariu; Giovanni Giuseppe Leoni; Dolors Izquierdo; Maria-Teresa Paramio; Luisa Bogliolo (Animals)
Suboptimal culture conditions during in vitro maturation (IVM) affect oocyte developmental competence and the viability of the resulting embryo. Three-dimensional (3D) culture systems provide a more biologically appropriate environment compared to traditional two-dimensional (2D) cultures. The aim of this study was to evaluate the effect of liquid marble (LM) microbioreactors as a 3D culture system on IVM and the subsequent embryo development of prepubertal goat oocytes. The cumulus–oocyte complexes (COCs) recovered from prepubertal goat ovaries underwent IVM in drops under oil (the 2D system and the control group) and in the 3D LM system (the LM group). After IVM, oocytes were parthenogenetically activated and cultured until the blastocyst stage. The control and LM groups showed similar rates of nuclear maturation (52.17% and 44.12%) and blastocyst formation (10.64% and 10.10%). Reactive oxygen species and glutathione levels and the density of transzonal projections (TZPs) in oocytes did not differ between groups. The LM system increased mitochondrial activity and modified the organization of these organelles in the oocyte cytoplasm compared to the control group. The LM microbioreactor demonstrated the ability to improve the mitochondrial status of the oocytes and was not harmful for oocyte IVM and subsequent embryo development. Therefore, LM could be used as a 3D cost-effective culture system for the IVM of prepubertal goat oocytes.